2017
DOI: 10.1186/s12889-017-4334-4
|View full text |Cite
|
Sign up to set email alerts
|

Do parents’ support behaviours predict whether or not their children get sufficient sleep? A cross-sectional study

Abstract: BackgroundSleep is an essential component of healthy cognitive and physical development. Lack of sleep may put children at risk for a variety of mental and physical health outcomes, including overweight, obesity and related chronic diseases. Given that children’s sleep duration has decreased in recent decades, there is a need to understand the determinants of child sleep, including the role of parental support behaviours. This study aims to determine the relative contribution of different types of parental sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 38 publications
2
39
1
2
Order By: Relevance
“…Our results showed that the proportion of students meeting sleep duration guidelines (89%) was considerably higher than in previous studies [7]. The existence of parental rules, oriented at increasing, or at least, at placing importance on adolescents' bedtime in this age group, could explain why all the adolescents in the different retained profiles met the sleep duration recommendations [57]. The number of students meeting guidelines for PA (21.4%) and screen time (1.7%) was lower than reported by previous international studies [7,46,58].…”
Section: Discussioncontrasting
confidence: 68%
“…Our results showed that the proportion of students meeting sleep duration guidelines (89%) was considerably higher than in previous studies [7]. The existence of parental rules, oriented at increasing, or at least, at placing importance on adolescents' bedtime in this age group, could explain why all the adolescents in the different retained profiles met the sleep duration recommendations [57]. The number of students meeting guidelines for PA (21.4%) and screen time (1.7%) was lower than reported by previous international studies [7,46,58].…”
Section: Discussioncontrasting
confidence: 68%
“…We emphasize that in the global sample, sleep problems are frequent, and may constitute an "invisible risk" for other problems (Carli, Hoven, Wasserman, Chiesa, Guffanti, & Sarchiapone, 2014). These results are in line with recent findings, which report the high frequency of sleep disturbances in today's Western society (Pyper, Harrington & Manson, 2017;Cheung, Bedford, Urabain, Karmiloff-Smith, & Smith, 2017). Therefore, we cannot ignore the sleep difficulties that these children have and we must reflect about the relationships between this general sleep poor quality and other types of behaviour and disturbances.…”
Section: Resultssupporting
confidence: 75%
“…Recent studies indicate that the sleep duration of children has decreased in the last few decades about 30 to 60 minutes, and it is important to understand the characteristics and restrictive factors for children's sleep, bringing in parental support behaviours to this understanding (Pyper, Harrington, & Manson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Parental support of sleep (Pyper, Harrington, & Manson, ), sedentary behaviour (Xu, Wen, & Rissel, ), and PA (Rhodes & Quinlan, ) has received much research attention, given that children and youth spend considerable time in the care of their parents. There are several different measures and conceptions of a construct as complex as parental support (Trost, McDonald, & Cohen, ), which is an umbrella term that represents the functional characteristics associated with the interactions between a parent and his/her children in promoting behaviours (Beets, Cardinal, & Alderman, ; Pyper, Harrington, & Manson, ).…”
Section: Introductionmentioning
confidence: 99%